Estimates of genetic and phenotypic parameters for carcass and meat traits of beef cattle - K.E. Gregory; L.V. Cundiff; R.M. Koch; M. Koohmaraie; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1994)
Data from nine parental breeds and three composite populations described in the preceding article were used to calculate heritabilities and phenotypic and genotypic correlations among carcass and meat traits. Phenotypic correlations indicated that marbling was a poor predictor of longissimus muscle palatability attributes of the individual carcasses. Heritability estimates were intermediate to high for fatness measures but generally low for palatability attributes. The high negative genetic correlation (-.56) between percentage of retail product and marbling score and the relatively low genetic correlations between percentage of retail product and palatability attributes suggest simultaneous selection for percentage of retail product and palatability, rather than for marbling score. Correlations among breed group means were generally high between measures of fatness and palatability attributes and were high and negative between percentage of retail product and marbling score or other fatness measures. Thus, opportunity is limited to select among breeds for high levels of marbling and a high percentage of retail product at the same time. The most logical approach to resolving that genetic antagonism is to form composites from breeds that contribute an optimum balance between favorable carcass composition and desirable meat palatability.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Carcass; Meat palatability; Heritabilities; Genectic correlations